A 2-set-up Routley-Meyer Semantics for the 4-valued Relevant Logic E4 - Robles, Gemma; López, Sandra M.; Blanco, José M.; Recio, Marcos M.; Paradela, Jesús R. (Bulletin of the Section of Logic, 2016)
The logic BN4 can be considered as the 4-valued logic of the relevant conditional and the logic E4, as the 4-valued logic of (relevant) entailment. The aim of this paper is to endow E4 with a 2-set-up Routley-Meyer semantics. It is proved that E4 is strongly sound and complete w.r.t. this semantics.